Biomechanical characterization of myofibrillar myopathies. (3rd December 2014) - Winter, Lilli; Goldmann, Wolfgang H.
Abstract : Myofibrillar myopathies (MFMs) are a group of sporadic and hereditary skeletal muscle diseases, which lead to severe physical disability and premature death. Most MFMs are caused by mutations in genes encoding desmin, plectin, VCP, filamin C, BAG3, FHL‐1, αB‐crystallin, DNAJB6, myotilin, and ZASP. Biomechanical studies on primary human myoblasts carrying desmin and plectin mutations showed increased stiffness and reduced mechanical stress tolerance i.e., higher mechanical vulnerability compared to control cells. Higher stiffness of mutant cells may lead to higher intracellular stress at physiologic stretch and shear deformation, which in turn could trigger muscle fiber degeneration.